Susan McHugh, Love in a Time of Slaughters: Human-Animal Stories Against Genocide and Extinction - Pick, Anat (Journal for the Study of Religion, Nature and Culture, 2022)
Susan McHugh, Love in a Time of Slaughters: Human-Animal Stories Against Genocide and Extinction (Philadelphia: Penn State University Press, 2019), 240pp., 32.95 (pbk), ISBN: 9780271083704.